2013
DOI: 10.1074/jbc.m113.466383
|View full text |Cite
|
Sign up to set email alerts
|

Small Oligomers of Ribulose-bisphosphate Carboxylase/Oxygenase (Rubisco) Activase Are Required for Biological Activity

Abstract: Background: Rubisco activase optimizes photosynthesis in plants, yet the arrangement of subunits is unclear. Results: The oligomeric state and biological function of Rubisco activase are dependent on protein concentration. Conclusion: Rubisco activase does not need to be hexameric for full activity. Significance: Understanding the functioning of Rubisco activase is an important step in determining how it regulates Rubisco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 58 publications
(86 reference statements)
3
42
0
Order By: Relevance
“…In this work, Rca hydrolytic activity was determined at a subunit concentration of 5 M, and in published works, the activity was measured utilizing 2 M Rca or less. A spike in ATPase activity has been reported to occur at 1-2 M subunit concentration, followed by a downward trend at somewhat higher concentrations (30). In support of this notion, preliminary data in our laboratory indicate a substantial reduction in turnover rate with increasing protein concentration.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this work, Rca hydrolytic activity was determined at a subunit concentration of 5 M, and in published works, the activity was measured utilizing 2 M Rca or less. A spike in ATPase activity has been reported to occur at 1-2 M subunit concentration, followed by a downward trend at somewhat higher concentrations (30). In support of this notion, preliminary data in our laboratory indicate a substantial reduction in turnover rate with increasing protein concentration.…”
Section: Discussionsupporting
confidence: 79%
“…Previous reports have shown that the minimal oligomeric unit for ATP hydrolysis consists of about three subunits (30,32). It is not surprising that the estimated stoichiometry for ATP hydrolysis is smaller than that for Rubisco reactivation, because in AAA ϩ proteins, active sites functional in hydrolysis are formed at the molecular interface of two subunits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although species-specific differences in Rca assembly remain poorly understood, it appears likely that significant differences in K d values exist. For example, SAXS data reported for tobacco apo-β-Rca at 2.4 μM were consistent with hexameric assemblies, 32 whereas cotton β-Rca-AC appears to require concentrations of ∼30 μM to form substantial amounts of hexamers. Below 500 nM, our data indicate that the β-Rca-AC monomer is the primary species in the presence of both ATPγS and ADP.…”
Section: ■ Discussionmentioning
confidence: 80%
“…All Rca isoforms presented with the concentration-dependent polydisperse oligomeric state typical for green-type Rca when analyzed by size exclusion chromatography (Supplemental Fig. S2; Blayney et al, 2011;Keown et al, 2013).…”
Section: Rubisco Activase From Agave Is Highly Functional At Activatimentioning
confidence: 99%